Catastrophic wildfires in the Pantanal wetlands as catalysts for transformative change - Martins Pereira, Alexandre de Matos; Damasceno-Junior, Geraldo Alves; Libonati, Renata; Anderson, Liana O.; Schlosser de Sá Teles, Jéssica; Villalobos, Roger; y otros autores más (2026)
Catastrophic wildfires, increasingly intensified by climate change and anthropogenic pressures, have emerged as critical drivers of socioecological transformation. This study examines the 2019–2020 wildfires in the Pantanal biome as a case of disruptive change, highlighting their role in catalyzing institutional, technological, scientific, and community-level innovations. Drawing on a transdisciplinary methodology and snowball sampling of key stakeholders, the research identifies rapid shifts in wildfire governance, including the implementation of inte grated fire management policies and the establishment of new scientific networks. Technological advancements, such as real-time fire monitoring systems and AI-driven early warning platforms, have enhanced fire detection and response capabilities. Concurrently, community resilience has been bolstered through the formation of local fire brigades, educational initiatives, and restoration programs supported by civil society and governmental actors. These responses reflect a convergence of adaptive and transformative strategies aimed at mitigating future wildfire risks. Despite these advances, sustaining long-term resilience remains contingent upon continued multilevel governance, cross-sectoral collaboration, and financial investment. The Pantanal experience derscores the potential of extreme events to disrupt entrenched systems and foster systemic change. However, it also reveals the complexities of maintaining momentum in the face of escalating climate threats. This analysis contributes to the broader discourse on disaster-induced transformation, emphasizing the need for integrated, inclusive, and anticipatory approaches to environmental governance in fire-prone landscapes.